Identification of Clinical Variants beyond the Exome in Inborn Errors of Metabolism - Soriano-Sexto, Alejandro; Gallego, Diana; Leal, Fátima; Castejón-Fernández, Natalia; Navarrete, Rosa; Alcaide, Patricia; Couce, María L.; Martín-Hernández, Elena; Quijada-Fraile, Pilar; Peña-Quintana, Luis; Yahyaoui, Raquel; Correcher, Patricia; et al. (International journal of molecular sciences, 2022)
Inborn errors of metabolism (IEM) constitute a huge group of rare diseases affecting 1 in every 1000 newborns. Next-generation sequencing has transformed the diagnosis of IEM, leading to its proposed use as a second-tier technology for confirming cases detected by clinical/biochemical studies or newborn screening. The diagnosis rate is, however, still not 100%. This paper reports the use of a personalized multi-omics (metabolomic, genomic and transcriptomic) pipeline plus functional genomics to aid in the genetic diagnosis of six unsolved cases, with a clinical and/or biochemical diagnosis of galactosemia, mucopolysaccharidosis type I (MPS I), maple syrup urine disease (MSUD), hyperphenylalaninemia (HPA), citrullinemia, or urea cycle deficiency. Eight novel variants in six genes were identified: six (four of them deep intronic) located in GALE, IDUA, PTS, ASS1 and OTC, all affecting the splicing process, and two located in the promoters of IDUA and PTS, thus affecting these genes’ expression. All the new variants were subjected to functional analysis to verify their pathogenic effects. This work underscores how the combination of different omics technologies and functional analysis can solve elusive cases in clinical practice.